THE USE OF RIBOSOMAL-PROTEOGLYCAN COMPLEX IN THE TREATMENT OF CHILDREN WITH FREQUENT RESPIRATORY INFECTIONS - V.V. Chernikov (Union of pediatricians of Russia, 2011)
Living in the industrialized countries is characterized by an increased number of respiratory infections among children, especially in recent years. In this case there is a group of children in which the frequency of such cases per year exceeds that of their coevals, so this contingent is referred to the group of sickly children. The paper presents the influence of the ribosomal-proteoglycan complex on the child's immune system to increase the resistance to the most common respiratory pathogens.Key words: frequently sick children, respiratory infections, immunomodulator, treatment, ribosamal-proteoglycan complex